Solusi pengelolaan sampah plastik: pembuatan ecobrick di kelurahan agrowisata, Kota Pekanbaru, Provinsi Riau - Aisyah Zumira; Hertien Koosbandiah Surtikanti (EcoProfit: Sustainable and Environment Business, 2023)
Indonesia is the second largest contributor of plastic waste in the world. In Indonesia, plastic waste is the second most common type after food waste. The increase in plastic waste is likely due to people's increasingly practical lifestyles and consumption patterns. Plastic and most other inorganic waste cannot be completely broken down by nature or decomposing microorganisms. The most significant contributors to waste in Indonesia are households, business centers, and traditional markets. This shows that households are important in discussing waste, both as producers and as agents of change in the future. One effort to reduce existing plastic waste is by making eco-bricks. Ecobricks are Polyethylene Terephthalate (PET) bottles filled with inorganic waste such as plastic, foam, packaging, and plastic. The benefits of eco-bricks are very diverse, such as reducing the amount of plastic waste, replacing bricks or building blocks, making various types of furniture, improving the community's economy, beautifying the environment, and using it in open spaces such as creating parks or buildings in the long term.